2013
DOI: 10.1016/j.econedurev.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Aid and Universal Primary Education

Abstract: Summary:Universal Primary Education (UPE) is one of the main objectives of development aid. However, very little empirical evidence of its effectiveness actually exists. Until very recently, the quality of available data was not sufficient to obtain robust results regarding the relationship between international aid and educational achievements. In this article, the latest, more disaggregated and more reliable data is used to study the relationship between aid to education and educational achievements. The foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Some aid disbursement data are available, but most multilateral donors, who are not required to report any of their activities to the CRS, report only their commitments and not their disbursements (d'Aiglepierre and Wagner, ). For example, during our main sample period (2003–08), the International Fund for Agricultural Development reported over $175 mn of commitments under purpose code 15150, but did not report any disbursements.…”
mentioning
confidence: 99%
“…Some aid disbursement data are available, but most multilateral donors, who are not required to report any of their activities to the CRS, report only their commitments and not their disbursements (d'Aiglepierre and Wagner, ). For example, during our main sample period (2003–08), the International Fund for Agricultural Development reported over $175 mn of commitments under purpose code 15150, but did not report any disbursements.…”
mentioning
confidence: 99%
“…Studies in education find that aid in the education sector has contributed to increased school enrolments and completion rates but in general only modestly (e.g. Arndt et al, 2014;Birchler and Michaelowa, 2013;Christensen et al, 2011;D'Aiglepierre and Wagner, 2013;Dreher et al, 2008;McGillivray et al, 2011). Of course, there is good reason to be suspicious of claims about improvements in school enrolment and completion rates.…”
Section: Aid and Poverty Education And Healthmentioning
confidence: 99%
“…At the same time, the recent literature suggests that analysing disaggregated aid and its impact on narrowly defined outcome variables offers a more promising way to assess the effectiveness of aid, compared to earlier studies on the economic growth effects of aggregate aid. In particular, it has been found that aid for education improved educational outcome variables such as enrolment rates (Dreher et al 2008) as well as completion rates, repetition rates, and gender parity (D'Aiglepierre and Wagner 2010). This provides an important channel through which aid for education could have promoted FDI in Latin America.…”
Section: Introductionmentioning
confidence: 99%